Current strategies and perspectives for active and passive immunization against Respiratory Syncytial Virus in childhood - Marcelo Comerlato Scotta; Renato Tetelbom Stein (Elsevier, 2023)
Objectives: Despite the global impact of the Respiratory Syncytial Virus (RSV) infection in children, only one monoclonal antibody (Palivizumab) has been approved for clinical use. However, advances in the knowledge of RSV immunology may enable the development of safe and effective new vaccines and monoclonal antibodies in a few years. The purpose of this review is to summarize available data on approved and developing passive and active immunizations against RSV in childhood and pregnancy. Data source: A non-systematic review of RSV immunoprophylaxis in childhood and pregnancy was carried out in PubMed, path.org and clinical trial registries, without language restrictions, up to September 2022. Data synthesis: Three monoclonal antibodies and 17 active immunization candidates are under development in phase 1 to 3 clinical studies. Regarding the first group, Nirsevimab is a monoclonal antibody with a prolonged half-life whose approval for clinical use is expected in the next months. Among the vaccines under development, six techniques are being used: protein subunit, viral particles, live attenuated virus, recombinant viral vector, chimeric, and mRNA. The first two approaches are being tested primarily in pregnancy, while the others are being developed for the pediatric population. Conclusions: The approval of extended half-life monoclonal antibodies is the next expected advance in RSV prevention, although the costs may be a barrier to the implementation. Regarding active immunizations, maternal and infant vaccination are complementary strategies and there are many promising candidates in clinical studies using different platforms.